Single-Incision Slings (SIS) – a New Option for the Surgical Treatment of Female Stress Urinary Incontinence - Naumann, G.; Albrich, S.; Skala, C.; Laterza, R.; Kölbl, H. (Geburtshilfe und Frauenheilkunde, 2012)
The new development of single-incision slings (SIS) for the treatment of female stress urinary incontinence offers comparable results with only minimal side effects and will find wide acceptance in modern incontinence surgery. This mini-sling is inserted over a single vaginal incision and fixed on both sides to the pelvic wall tissue with special anchors, without passing through the groin and avoiding a blind tape passage. Compared with the established sub-urethral tapes, there are comparable success rates with fewer complications. Randomised prospective studies are needed to evaluate whether, in the long run, the benefits of the single incision technique can be correlated with satisfying continence results.
Keywords: single incision sling; success rate; complications; new surgery